The stratigraphy of alibonca formation and its relationship with Malatya volcanites in the Southwestern Arapgir (Malatya, Turkey) - Sönmez, Mustafa; Aksoy, Ercan (International Multidisciplinary Scientific Geoconference, 2017)
The main purpose of this article is to reveal the age of Alibonca Formation and Malatya Volcanites, their formational environment and the contact relationship between these two units. The units that cropped out in the study area are Keban Metamorphites (Permo-Trias), Alibonca Formation (Lower Miocene), Malatya Volcanites (Lower-Upper Miocene), Meteristepe formation (Lower Pleistocene), Yoncalı formation (Upper Pleistocene), talus and alluviums (Holocene-current). Alibonca Formation is composed of medium-thick bedded limestone that is the product of carbonate platform. The unit also comprises mudstone containing clay-rich limestone, marl and coal strata that deposited on the lagoons connected to the Miocene Sea that the limestone deposited on. The unit unconformably overlying different bases was formed in the Aquitanian- Burdigalian period when the region fell under transgression effect. The Lower-Upper Miocene aged Malatya Volcanites are composed of agglomerate, tuff lapilli and lava flows with dacitic, andesitic and basaltic composition crossing them. There is a transitional and concordant contact between Alibonca Formation and Malatya Volcanites. The volcanism leading to the formation of Malatya Volcanites began in the last phases of the sedimentation of Alibonca Formation that deposited on a transgressive sea in the Lower Miocene. © SGEM2017. All Rights Reserved.
17th International Multidisciplinary Scientific Geoconference, SGEM 2017 -- 29 June 2017 through 5 July 2017 -- Albena -- 130787
Keywords: Alibonca formation; Malatya; Malatya volkanites; Stratigraphy